2003
DOI: 10.1182/blood-2002-05-1338
|View full text |Cite
|
Sign up to set email alerts
|

Albumin-expressing hepatocyte-like cells develop in the livers of immune-deficient mice that received transplants of highly purified human hematopoietic stem cells

Abstract: Rodent bone marrow cells can contribute to liver. If these findings are applicable to humans, marrow stem cells could theoretically be harvested from a patient and used to repair his/her damaged liver. To explore this potential, CD34(+) or highly purified CD34(+)CD38(-)CD7(-) human hematopoietic stem cells from umbilical cord blood and bone marrow were transplanted into immunodeficient mice. One month after transplantation, carbon tetrachloride (CCl(4)) was administered into the mice to induce liver damage and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
173
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(184 citation statements)
references
References 45 publications
(41 reference statements)
10
173
0
1
Order By: Relevance
“…Recently, it has been suggested to be effective in inducing hepatocytic differentiation of BMC (11). Four female B6 mice were lethally irradiated and transplanted with male TgN(ActbEGFP) or TgN(MTnLacZ) BM mononuclear cells (1 ϫ 10 6 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been suggested to be effective in inducing hepatocytic differentiation of BMC (11). Four female B6 mice were lethally irradiated and transplanted with male TgN(ActbEGFP) or TgN(MTnLacZ) BM mononuclear cells (1 ϫ 10 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…We used three models: T here have been a number of reports that show the potential of adult rodent bone marrow (BM) cells (BMCs) to transdifferentiate into a variety of cell types (1-7), including hepatocytes (8 -10). One of the best examples for the transdifferentiation has been the ability of BM-derived hapatocytes to repopulate the liver of mice with fumarylacetoacetate hydrolase knockout mouse (FAHϪ͞Ϫ) and correct the liver disease (10), although recent reports have shown that this correction of liver disease is caused by fusion of donor BM to recipient hepatocytes rather than transdifferentiation (11,12). However, it is not fully elucidated whether or not the significant level of the contribution of BM-derived hepatocytes in the FAHϪ͞Ϫ model, either in the form of transdifferentiation or cell fusion, can be generalized in other liver injury models.…”
mentioning
confidence: 99%
“…Whether the CD34 ϩ Lin Ϫ cells derived from CB have the potential to transdifferentiate into other types of nonhematopoietic tissues in the fetal stage remains largely unexplored. Wang et al (27) reported that human albumin-expressing hepatocyte-like cells can be developed in the livers of immune-deficient and CCl 4 -injured mice that received transplants of human HSC, suggesting that human ''hematopoietic'' stem͞progenitor cells have the capacity to respond to the injured liver microenvironment by inducing albumin. A more recent study reported that human HSCs can efficiently (20%) generate functional hepatic cells in the human͞sheep model (28).…”
Section: Discussionmentioning
confidence: 99%
“…Although the therapeutic effect of stem cell transplantation is promising, previous studies have suggested that less than 1% of transplanted MSCs are constituted to the total organ mass. 25,26 The fate of stem cells after transplantation remains an important issue. In our study, we also encountered the same problem.…”
Section: Discussionmentioning
confidence: 99%